FIFA's Role in International Sports Diplomacy : Does Its Positive Influence in Fostering Diplomacy and Social Equality Outweigh Corruption Scandals? - Barnáš, Ondřej; Kočí, Kateřina; Rolenc, Jan Martin, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis examines the extent to which the positive impact of international sports organizations on diplomacy and social equality can outweigh the harm caused by governance failures, using the example of the football organization FIFA. Since the corruption scandals of 2015, FIFA has sought to restore its legitimacy through campaigns, strategic initiatives and partnerships promoting inclusion, anti-discrimination and gender equality. However, many of these efforts have been criticized for remaining at a symbolic level with limited evidence of structural reforms. The theoretical framework is based on the concepts of soft power, sports diplomacy, institutional isomorphism and hybrid governance, which are applied to assess FIFA’s activities not only as a sports regulator but also as a global non-state actor with diplomatic functions. The study uses a qualitative content analysis of FIFA’s official documents, speeches, campaigns and programmes from 2015 to 2023, focusing on three main areas: public communications, internal strategic initiatives such as the FIFA Strategy for Women’s Football, and external collaboration, in particular with UN Women. The findings show that while FIFA projects a strong normative image and articulates measurable equality targets, the lack of enforcement and accountability mechanisms undermines the credibility and long-term effectiveness of its efforts. The paper concludes that FIFA’s initiatives reflect elements of symbolic soft power and normative isomorphism, but are constrained by a hybrid governance model that emphasizes voluntary compliance. As a result, the organization’s positive impact remains limited by its unresolved internal governance challenges.
Vedoucí práce: Kateřina Kočí
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses